PENGARUH AUDIT OPERASIONAL DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PELAYANAN KESEHATAN INSTALASI RAWAT INAP RUMAH SAKIT (STUDI PADA RUMAH SAKIT MILIK PEMERINTAH DI PEKANBARU) - ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 4 No 4 (2020): Bilancia : Jurnal Ilmiah Akuntansi, 2020)
This study aims to find out about (1) the effect of operational audits on the effectiveness of inpatient health care services in Government-Owned Hospitals in Pekanbaru, (2) the effect of internal control on the effectiveness of inpatient health care services at Government-Owned Hospitals in Pekanbaru. This study uses primary data by distributing questionnaires to the intended respondents. The population in this study is a government-owned hospital in Pekanbaru. All of these populations are directly used as research samples. There are 8 government-owned hospitals in Pekanbaru that are used as research samples. Hypothesis testing is done by using partial testing (t test) to determine whether the variables that occur in the study sample are influenced by operational auditing and internal control significantly influence the effectiveness of health services. The statistical test aids used are SPSS version 23.0. The results showed that operational audit and internal control had an effect on the effectiveness of hospital services. Operational audit has a significant effect (0,000 <0.05) and internal control has a significant effect (0,000 <0.05). R square value is 0.508 which means that 50.8% of the effectiveness of health service variables can influence operational audits and internal controls.